The Relationship Between Cybersecurity and Public Trust in Digital Services Based on Fintech Lending Applications - Harry Sudhana; Dhian Tyas Untari; Ahmad Syarif; Nyayu Maya Ardini; Muhammad Firman Maulana; Pandri Zulfikar (Citakonsultindo, 2026)
The rapid growth of fintech lending applications has significantly transformed access to financial services, especially in developing countries. These platforms provide fast, convenient, and accessible financial solutions; however, they also raise critical concerns regarding cybersecurity and data protection. This study aims to analyze the relationship between cybersecurity and public trust in digital lending applications through a qualitative literature review. Cybersecurity is a key determinant of trust, as users must share sensitive personal and financial information when accessing digital lending services. Empirical studies indicate that data breaches, unauthorized access, and misuse of personal data significantly reduce consumer trust. Conversely, strong cybersecurity mechanisms such as encryption, authentication systems, and regulatory compliance enhance trust and encourage adoption This paper finds that cybersecurity is not only a technical requirement but also a strategic factor in building sustainable trust relationships between users and fintech providers. Strengthening cybersecurity frameworks, improving regulatory enforcement, and increasing digital literacy are essential to fostering trust in digital lending ecosystems. The study contributes to the understanding of how cybersecurity influences trust and provides insights for policymakers and fintech providers in developing secure and reliable digital financial services. Keywords: Cybersecurity, Fintech Lending, Digital Trust, Data Protection, User Behavior